Diversity of aquatic insects on the leaf litter of water lettuce (Pistia stratiotes L.) in an experimental fishpond - Hamdhani, Hamdhani; Fadhilla, Febby Nur; Eryati, Ristiana (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Aquatic insects play a crucial role in ecological systems because they are sensitive to environmental changes, indicating whether an environment is healthy or polluted. The vast biodiversity in morphology, physiology, and adaptive behavior among insect species on Earth has led to numerous scientific studies using insects as models. Population dynamics studies, for instance, often rely on the evolution of insect populations. The objective of this research is to explore the types of aquatic insects present, as well as their diversity, evenness, and dominance levels. The study found 4 orders and 4 families totaling 180 individuals on the leaf litter of water lettuce. The diversity index of aquatic insects on the water lettuce leaf litter was categorized as low. The evenness index was categorized as small. The dominance index ranged from low to moderate to high categories.